Supplementation Of Analog Rice İn Combination With Metformin Prevent Myocardial Cell Death İn Type 2 Diabetuc Rats - Muhammad, Andi; Firdaus, Jauhar; Rumastika, Nindya Shinta; Hairrudin, Hairrudin; Sakinah, Elly Nurus (International Journal of Health and Information System, 2025)
Type 2 diabetes (T2D) is an urgent health issue that leads to one of the most significant cardiovascular complications worldwide, diabetic cardiomyopathy (DCM), which is associated with high morbidity and mortality. Chronic hyperglycemia and oxidative stress are major contributor for DCM. Analog rice based of MOCAF and corn starch is a functional food recommended as nutritional supplementation to replace staple foods in T2D patients. Analog rice has a high fiber content, high resistant starch and low glycemic index, which can help lower blood sugar levels and prevent DM complications. MOCAF in analog rice is also rich in phenolic compounds, which has potential effect of antioxidant. Metformin is the first line oral therapy for T2D. The present study investigates the potential effects of an analog rice diet in combination with metformin, for the development of DCM. Type 2 diabetic rats were induced by HFD/STZ method and was treated by analog rice and metformin for 4 weeks. Myocardial cell death measured by pyknotic nuclei percentage was analysed. The study result demonstrate that analog rice and metformin prevent the myocardial cell damage observed in type 2 diabetic animals, highlighting analog rice potential as adjuvant therapy, for treating DCM has no clinical significance than metformin therapy alone.